IL‐17 and its role in inflammatory, autoimmune, and oncological skin diseases: state of art. (30th October 2019) - Bernardini, Nicoletta; Skroza, Nevena; Tolino, Ersilia; Mambrin, Alessandra; Anzalone, Alessia; Balduzzi, Veronica; Colapietra, Daniela; Marchesiello, Anna; Michelini, Simone; Proietti, Ilaria; Potenza, Concetta
Abstract: Recent data support the theory of the involvement of IL‐17 in the pathogenesis of several chronic inflammatory skin diseases (psoriasis, atopic dermatitis, acne, hidradenitis suppurativa) and autoimmune skin diseases (alopecia areata, vitiligo, bullous diseases). Even if the role of IL‐17 in inflammatory and autoimmune diseases has been reported extensively, its role in tumor is still controversial. Some reports show that Th17 cells eradicate tumors, while others reveal that they promote the initiation and early growth of tumors. Herein, we review the role of IL‐17 in the involvement of some common dermatologic diseases: psoriasis, atopic dermatitis, hidradenitis suppurativa, acne, vitiligo, melanoma, and nonmelanoma skin cancers.